Effect of different surface treatments on the alteration of color of ceramic - Jessica Bedoya Ocampo; Jessica Bedoya Ocampo; Carlos Andrés Solano Macías; Andrea Bedoya Ocampo (Kiru)
Objective: The objective of this study was to evaluate the effect of different surface treatments on the pigmentability of the ceramic after immersion in staining solution. Materials and Methods: 44 disks of 10 mm radius and 3 mm thickness were made. Samples were randomly assigned among 4 experimental groups (n=11) receiving surface treatment according to the different groups M, H, B, L. (n=10) were distributed for color evaluation and Roughness (RU) and a sample of each group used for scanning electron microscopy (SEM) analysis. For (RU), the data were subjected to ANOVA on ranks (α=0.05), and for the color ANOVA a factor (α=0.05). In the microphotographs of the surface, a qualitative/descriptive analysis was carried out. Results: In the (RU) compared before and after immersion for each group, no statistical difference was observed (p> 0.05). When comparing the types of polish before immersion, a difference was observed between the L group with the other M, H, B (p <0.05). In the analysis of the groups after immersion, there was a difference of group L with B and M (p <0.05). When comparing the color alteration, after immersion, there was a difference between all the ANOVA groups (p <0.05). In the analysis by (SEM) all groups had partially porous surfaces; however, the varnishes produced the best result groups H and B. Conclusions: The texture of the surface is an important factor in the pigmentability of ceramics. the varnished materials showed less color alteration